Improving the Fourth Wave of Coffee in Sustaining the Coffee Value Chain as Economic Growth in Istanbul - Kurniawan Arif Maspul (CV. Ulil Albab Corp, 2023)
Istanbul is well-known for its history, culture, and cuisine, particularly in the food and beverage industry. The expansion of Istanbul's gastronomy industry has created opportunities for small and medium-sized enterprises (SMEs) to contribute to the local economy by developing and promoting local cuisine. Sustainable development in the creative economy sector, particularly in the food and beverage industry, can create a one-stop gastronomy value chain, with stakeholders working together to reinforce each other's ideas and promote long-term growth. Similarly, the development of coffee in Istanbul has increased in recent years, making it a destination for specialty coffee in Asia and Europe. The unique characteristics of Istanbul make the local SME economy dynamic in its rotation, creating the possibility of long-term growth. This study used qualitative research methods such as observations, interviews, and document analysis to present perceptions and events in a realistic and integrated manner. The study focused on the third batch of coffee roasteries in Istanbul, and data was gathered through interviews with four coffee professionals from Istanbul's leading specialty coffee roasters. The data were descriptively analysed to identify the perspectives of people directly involved with professional coffee, namely four coffee roasters, who are the primary source of information and directly related to Istanbul's coffee value chain cycle. Coffee tourism can help the local coffee economy. Promoting fair trade practices, responsible coffee production, gender equality, decent work opportunities, and responsible consumption and production in Istanbul's coffee value chain can help achieve the United Nations' Sustainable Development Goals (SDGs). Istanbul's creative economy sector is thriving and has the potential to contribute to the local economy for many years to come. Istanbul's gastronomy and coffee industries can continue to grow and offer unique experiences to locals and tourists by promoting sustainability and working together as stakeholders.